К реконструкции пресса античной винодельни на Темир-горе - Андрющенко, Н.П. (Боспорские исследования, 2009)
The ancient winery on Temyr Mountain was one of the first wineries excavated on the territory of the north Pontic area. In 1870, A.E.Lyutsenko made archaeological research of this monument but he could not identify the remains of the ancient construction correctly. Only in the 30s of the 20th century V.F.Gaidukevich put that ancient winery into scientific circulation. Performed graphic reconstruction of the press equipment of the winery on Temyr Mountain gives a new idea of this ancient monument.